1991
DOI: 10.1111/j.1600-0765.1991.tb01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell attachment activity of cementum: bone sialoprotein _ identified in cementum

Abstract: Considerable research effort has been directed at preparing root surfaces in a fashion that would promote cell attachment leading to periodontal regeneration; however, no methods have proven to be clinically predictable. Identification of attachment protein(s) associated with the root surface matrix of cementum may prove valuable for developing effective clinical treatments. In this study cementum proteins were extracted from bovine and human teeth by sequential chaotropic extraction using guanidine followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 27 publications
2
38
0
1
Order By: Relevance
“…Western blots revealed the presence of three broad bands cross-reacting with an antibody to bonesialoprotein II. This result confirmed the recent observations of Somerman et al (1991), who reported the presence of bonesialoprotein II in guanidine-EDTA extracts. The p68 was in the region of one of these bands, although additional experiments are necessary to determine whether it is bone sialoprotein.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Western blots revealed the presence of three broad bands cross-reacting with an antibody to bonesialoprotein II. This result confirmed the recent observations of Somerman et al (1991), who reported the presence of bonesialoprotein II in guanidine-EDTA extracts. The p68 was in the region of one of these bands, although additional experiments are necessary to determine whether it is bone sialoprotein.…”
Section: Discussionsupporting
confidence: 95%
“…However, the time courses of attachment are similar for both proteins (McAllister et al, 1990). Both fibronectin and cementum proteins mediate cell attachment through the arg-gly-asp peptide sequence (McAllister et al, 1990;Somerman et al, 1991), and whether the same cell-surface receptors are involved is not clear. Interestingly, epithelial cells did not attach significantly to plates treated with cementum proteins under the conditions of assay, indicating that healthy root surfaces favor the attachment of fibroblasts over epithelial cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…BSP has been detected in dentin extracts (Fisher et al, 1983) and BSP mRNA expression shown in odontoblasts (Chen et al, 1991). BSP has also been identified in cementum (Somerman et al, 1991). Dentin contains a 53-kDa sialoprotein termed DSP (dentin sialoprotein), which is rich in sialic acid and appears to be specific to dentin D'Souza et al, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…The cementum, which is continuously deposited and rarely remodeled, is an important component of periodontium and also contains various proteins which facilitate cell migration, attachment, differentiation and proliferation (1)(2)(3). Progression of plaque-induced chronic inflammatory periodontal disease leads to continuous loss of periodontal attachment and exposure of the root cementum to the oral environment.…”
Section: Introductionmentioning
confidence: 99%